Comparative study on surgical outcome for benign vocal cord lesions by conventional method versus coblation - Sundarm, Muthuchitra; Krishnaswamy, Semmanaselvan; Kumar, Sanjay; Mohideen, Shaikh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Benign vocal cord lesions are common laryngeal pathology found in routine clinical practice.microlaryngeal surgery is useful in excision for pathology. Coblation assisted microlaryngeal surgery is a new technique for the vocal cord lesions Methods: Current study was conducted in Government Kilpauk medical college hospital and Government Royapettah hospital from the period of 2018 to 2019 in 40 patients with benign vocal cord lesion. The objectives of current study were to assess the voice handicap Index before and after surgery, to assess the surgical benefits and ease in doing the procedure intraoperatively and to assess the postoperative recovery in conventional micro laryngeal procedure. Results: The overall analysis shows coblation being an evolving technique has advantages over the conventional cold knife method. Blood loss and the surgery duration was less in coblation. But the assessment tools of both voice handicap index, voice analysisand GRBASscore favours conventional micro laryngeal surgery with reduced scores and improvement in performance with statistically significant values probably due to minimal tissue handling and decrease in post op scarring in conventional micro laryngeal surgery. Conclusions: The overall voice handicap index and voice analysis showed improvement post operatively in both the groups with more favoring response to conventional method with statistically significant values. In the same away the GRBAS score also favors the conventional method. Coblation being a newer technique can be employed for surgical treatment for micro-laryngeal surgery considering its advantages and less time consumption. Stroboscopy and other acoustic analysis along with long term follow up is needed.